C61(COOH)2 interacting with the antiviral ribavirin - Vendrame, Laura; Fagan, Solange Binotto; Zanella, Ivana (Disciplinarum Scientia | Naturais e Tecnológicas, 2017)
Carbon nanostructures present unique properties that result from a variety of possible structural forms. Therefore, the application of such systems, in a functionalized or pristine form, as chemical or biological sensors have become a large field of study and application. Among the C60 derivatives, the C61(COOH)2, has shown success crossing the external cell membrane. This makes the compound, in biological environment, ideal for drug delivery systems. In this work the interaction of C61(COOH)2 with antiviral ribavirin was performed through ab initio simulations using the SIESTA code. The antiviral ribavirin is used for the treatment of chronic hepatitis C and, recently it has been used for the canine distemper disease. However, the delivery of the ribavirin in the central nervous system (CNS) still faces challenges due to its low penetration in the blood brain barrier (BBB). The results show that the ribavirin interact weakly with C61(COOH)2 molecules. The interaction occurs through a physisorption regime, with values between 0.17 and 1.12 eV for the most stable configurations. This type of interaction is interesting so that the absorbent system remains connected to its carrier (in this case the C61(COOH)2) with no alteration in the properties of pristine molecules.